Do Long-Term Swings in the Dollar Affect Estimates of the Risk Premia? - Evans, Martin D.D.; Lewis, Karen K. (Review of Financial Studies, 1995)
Foreign exchange returns exhibit behavior difficult to reconcile with standard theoretical models. This article asks whether the recent findings of long swings in exchange rates between appreciating and depreciating periods affect estimates of the foreign exchange risk premium. We demonstrate how the “peso problem” introduced by expected shifts in exchange rate regimes can affect inferences about the risk premium in at least two ways: (1) it can make the foreign exchange risk premium appear to contain a permanent disturbance when it does not; and (2) it can induce bias in the foreign exchange return regressions such as in Fama (1984).